W sprawie tzw. miecza jednosiecznego - Horbacz, Tadeusz J. (Acta Universitatis Lodziensis. Folia Archaeologica, 1982)
The author points at the necessity of revision of the term "single-edged sword" as used in the Polish archeological terminology. The term "single-edged sword" used to describe pieces of single-edged side-arms, becoming more and more popular in the middle La-Tené period in Pomerania and nearby areas were gradually accepted by the population of the Przeworsk culture, among which they survived till the early Roman period. Stating the existence of an essential mistake in the term, being a result of literary translation of a German term (ein schneidiges Schwert), the author proposes that it should be replaced with one of the names used for elements of arms and accepted in the Polish literature dealing with arms (sax, chopper, dagger, cutlass). Analysis of features of specimens called these names shows that the term "cutlass" would be most appropriate. This kind of single-edged weapon is characterized with features typical for the so-called single-edged swords. Cutlassess have asymmetric, slanting hilt. Linings made from organic materials are perpendic ularly fastened to the tang with rivets, the so-called rivetting perpendicular to the edge (unlike the so-called rivetting on the tang met e.g. on choppers ans saxes). The pommel in specimens of this type is usually straight. Replacing the term "single-edged sword" with the term" cutlass" – apart from cognitive merits – would approach the terminology used by archeologists to general concept sapplied in literature dealing with arms, which are more precise and explicit. This will also allow to abandon the term "two-edged sword" which also is an exact translation of a German term (zweischneidiges Schwert) by skipping the adjective part of the term. A sword is a type of two-edged side-arms and this fact need not be stressed additionally. The author stresses also the need for analysis of the genesis of the so-called single-edged sword. It is accepted in the literature that prototypes for specimens from the Middle La-Tené period were forms of single-edged side-arms belonging to the Pomeranian culture. The problem seems, however, to be more difficult. Single-edged side-arms, in separably accompanying the sword in prehistory, represent a parallel developmental continuation. Relationships between their particular types are clearly much less obvious than in the case of two-edged weapons. The prototype was undoubtedly a knife while development of its combat forms might have been taking place quite independently. This continues to be an open problem calling for further analysis.